Teacher's Efforts in Improving Students' Learning Interest in PPKn Subjects at State Middle School 2 West Biak - Nap, Ruth Priskila; Elizabet Kafiar; Stevanus Mandowen (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe teachers' efforts to increase student learning interest in Pancasila and Citizenship Education (PPKn) in seventh-grade students at SMP Negeri 2 Biak Barat. This study used a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and questionnaires. The subjects were PPKN teachers and seventh-grade students. The results showed that the learning process was still dominated by conventional methods, namely lectures and question-and-answer sessions, with limited use of learning media. Questionnaire analysis showed that students' learning interest was in the moderate category, with an average score of 3.05. Most students felt bored due to the lack of varied learning methods and engaging learning media. Teachers provided motivation through verbal praise and additional credit, but these forms of reinforcement were not sufficient to increase learning interest overall. Based on these findings, it can be concluded that teachers' efforts to increase students' learning interest in PPKN need to be improved through the application of varied learning methods, the use of visual media, and consistent motivation and rewards. This research is expected to serve as a reference for teachers and schools in designing more interactive and contextual PPKN learning.